Modelagem dinâmica do escoamento de um sistema de elevação por plunger lift - Assmann, Felipe Pinheiro Mota (2012)
A critical problem in mature gas wells is the liquid loading. As the reservoir pressure decreases, gas superficial velocities decreases and the drag exerted on the liquid phase may become insufficient to bring all the liquid to the surface. Liquid starts to drain downward, flooding the well and increasing the backpressure which decreases the gas superficial velocity and so on. A popular method to remedy this problem is the Plunger Lift. This method consists of dropping the "plunger"to the bottom of the tubing well with the main production valve closed. When the plunger reaches the well bottom the production valve is opened and the plunger carry the liquid to the surface. However, models presented in literature for predicting the behavior in plunger lift are simplistic, in many cases static (not considering the transient effects). Therefore work presents the development and validation of a numerical algorithm to solve one-dimensional compressible in gas wells using the Finite Volume Method and PRIME techniques for treating coupling of pressure and velocity fields. The code will be then used to develop a dynamic model for the plunger lift which includes the transient compressible flow within the well